Analisis Kemampuan Koneksi Matematis Mahasiswa ditinjau dari Self Regulated Learning(SRL) pada Pembelajaran Daring - Anwar, Syahrul; Juniawan, Egi Adha; Pamungkas, Aan Subhan (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2021)
This study aims to examine the ability of mathematical connections to be viewed from independent learning (SRL) in learning flat geometry courses. One class sample, namely second-semester students, collected 26 people, the mathematics education study program STKIP La Tansa Mashiro Rangkasbitung-Lebak, the 2020/2021 academic year. This type of research is descriptive qualitative chosen because it aims to describe the ability of students to solve math problems independently. The instrument used in this study is 30 questions for high, medium and low-level SRL, aiming to determine student learning independence. In contrast, five questions are given through the WhatsApp class group for the test instrument for mathematical connection abilities used in descriptions. The subjects in this study were selected based on active students and had good grades during bold learning activities. Then the interview test process was carried out six about the explanation between the researcher and the research subject. The results of the analysis of students' mathematical connection abilities, the mean value of the complete subject type SRL group = 96 with a score of 100%, moderate SRL of semi-complete type = 92.67 with a score of 90%, and Low SRL of incomplete type = 91 .67 with a score of 80%. Based on this, it shows that the value of the SRL category (high, medium, low) in the bold learning done after the analysis significantly affects the students' mathematical connection abilities.